ANALISIS EFEKTIVITAS SP4N-LAPOR! DALAM MENINGKATKAN PELAYANAN PUBLIK DI KABUPATEN TANGERANG - Ahmad Aziz Ardiansah; Yusuf Fadli; Ahmad Chumeidi; Dharma Hermawan (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This study aims to evaluate the effectiveness of the National Public Service Complaint Management System - People's Online Aspiration and Complaint Service (SP4N-LAPOR!) in improving the quality of public services in Tangerang Regency by overcoming problems such as the low effectiveness of handling public complaints, low public participation in service supervision, coordination between agencies, and the need for more modern, responsive, and quality services. SP4N-LAPOR! It is a digital platform that facilitates the public in conveying complaints and aspirations regarding public services. The theory used in this study is the SERVQUAL model theory or service quality which consists of 5 aspects, including tangibles (direct evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee), and empathy (empathy). Descriptive qualitative method, data was collected from interviews with stakeholders, app users, and social media and news analysis. The results of the study showed that the effectiveness of SP4N-LAPOR! in public services in Tangerang Regency is quite significant, especially in increasing the accessibility and speed of government response to public complaints. This application has made it easier for the public to submit complaints and get faster follow-up, with the support of commitment from the local government and the supervision of the Ombudsman of the Republic of Indonesia. However, the effectiveness still needs to be improved, considering that most of the application users are immigrants, and the new socialization reaches the village level. The recommendation of this study is the need for continuous improvement in socialization and education on the use of SP4N-LAPOR! As well as collaborating with various parties such as private agencies, educational institutions, and community leaders to ensure that more residents can access and utilize this service. Local governments are also advised to maintain active communication and be responsive to public input, in order to continuously improve the systems and services provided, and ensure that all complaints are responded to with empathy and attention.